Kajian Pelaksanaan Intervensi Gizi Spesifik di Desa Naitae Kecamatan Fatuleu Barat Tahun 2023 - Ebzan Akwila Laikingis (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
This study aims to assess the implementation of specific nutrition interventions in an effort to accelerate stunting reduction in Naitae Village, West Fatuleu Sub-district, Kupang Regency in 2023, as well as identify barriers and opportunities for improvement. The research method used was a qualitative approach with a case study design. Data were collected through in-depth interviews with key informants such as the Head of Puskesmas, program managers, Village Head, Posyandu cadres, pregnant women, and mothers of stunted toddlers and those who have completed the intervention. Data were analyzed using thematic analysis techniques through a process of categorization and source triangulation. The results showed that specific nutrition interventions in Naitae Village include the provision of Blood Addition Tablets (TTD), antenatal examinations, complete basic immunization, deworming, macronutrient supplements (PMT). The implementation of these interventions is generally in accordance with national guidelines, but there are still various barriers, such as unreachability of adolescent girls who are not in school, low compliance of pregnant women in consuming TTD, and limited access to services due to distance and local culture. In conclusion, although the intervention was implemented according to procedures, the success of the program was still constrained by individual, geographical, and socio-cultural factors. Efforts to increase education and cross-sector collaboration are needed to accelerate stunting reduction in the region.